A new titanosaur (Dinosauria, Sauropoda) from the Upper Cretaceous of Mendoza Province, Argentina (Ameghiniana, 2013)
Abstract. Mendozasaurus neguyelap gen. et sp. nov. is a new titanosaur from the Upper Cretaceous of Neuquén Basin and the first known dinosaur species from Mendoza Province, Argentina. The remains were found in levels provisionally referred to the Río Neuquén Formation (late Turonian-late Coniacian) of the Neuquén Group. They consist of 22 mostly articulated caudal vertebrae, a dorsal vertebra, numerous disarticulated appendicular bones and osteoderms. Autapomorphies of Mendozasaurusare: (1) subtriangular infrapostzygapophyseal fossae in anterior dorsal vertebrae; (2) postzygapostspinal laminae parallel to the plane of the postzygapophyseal facets in anterior dorsal vertebrae; (3) interzygapophyseal cavity dorsoventrally extended and limited by the spinopostzygapophyseal and spinoprezygapophyseal laminae in anterior caudal vertebrae; (4) middle caudal vertebrae slightly procoelous with reduced posterior condyles displaced dorsally; (5) laminar mid-posterior caudal neural spines with horizontal and straight dorsal border, and anterodorsal corner forming a right angle; (6) large subconic-spherical osteoderms lacking cingulum. A cladistic analysis permits the inclusion of Mendozasaurus within Titanosauridae, according to the phylogenetic definition of this clade. Although this new species exhibits almost all the titanosaurid synapomorphies proposed by some authors, it lacks prominent posterior condyles in middle caudal centra. This and other plesiomorphic traits suggest that Mendozasaurus is a basal titanosaurid, more derived than Malawisaurusin the caudal procoely.Resumen. UN NUEVO TITANOSAURIO (DINOSAURIA, SAUROPODA) DEL CRETÁCICO SUPERIOR DE LA PROVINCIA DE MENDOZA, ARGENTINA. Mendozasaurus neguyelap nov. gen. et sp. es un nuevo titanosaurio del Cretácico Superior de la Cuenca Neuquina y la primera especie de dinosaurio proveniente de la provincia de Mendoza, Argentina. Procede de niveles asignados preliminarmente a la Formación Río Neuquén (Turoniano tardío-Coniaciano tardío) del Grupo Neuquén. Está representado por 22 vértebras caudales en su mayoría articuladas y numerosos restos desarticulados: una vértebra dorsal, arcos hemales, huesos apendiculares y grandes osteodermos. Son autapomorfías de Mendozasaurus: (1) fosas infrapostzigapofisiales subtriangulares en vértebras dorsales anteriores; (2) láminas postzigapostespinales paralelas a los planos de las facetas articulares de las postzigapófisis en vértebras dorsales anteriores; (3) cavidad interzigapofisial dorsoventralmente extendida y limitada por las láminas espinopostzigapofisial y espinoprezigapofisial en vértebras caudales anteriores; (4) centros caudales medios suavemente procélicos con cóndilos posteriores reducidos y desplazados dorsalmente; (5) espinas neurales de vértebras caudales medias-posteriores laminares y anteroposteriormente elongadas, con un borde dorsal horizontal y un ángulo ánterodorsal recto y (6) grandes osteodermos subcónicos-subesféricos sin cingulum. Un análisis cladístico permite incluir a Mendozasaurusdentro de Titanosauridae, según definiciones filogenéticas de este clado. Si bien exhibe casi todas las sinapomorfías propuestas por algunos autores para caracterizar a Titanosauridae, carece de cóndilos posteriores prominentes en sus vértebras caudales medias. Éste y otros caracteres plesiomórficos sugieren que Mendozasaurus es un titanosáurido basal, más derivado que Malawisaurusen su procelia caudal.